Kuning in karo Community: Medical Anthroplogy Study in Bunuraya Village, Tiga Panah District, Karo Regency - Roseva Sari Br Bangun; Sabariah Bangun (Indonesian Journal of Medical Anthropology, 2021)
This research discusses the cultural heritage of one of the ethnic groups in Indonesia, such as the new traditional medicine, namely Kuning. The purpose of this study is to describe the presence of Kuning in the Karo community and its benefits for the community so that it is maintained as one of the traditional Karo medicines. This research is a descriptive type with a qualitative approach. The method used in data collection is occasional participatory observation and interviews, the baseline information is the village head, the key information is traditional leaders and people who have lived in Bunung Raya for a long time, from the usual information is the Kuning maker and the Kuning user. The result of Kuning’s research is that traditional Karo medicine made from a mixture of various herbs has fewer negative side effects when compared to modern medicine and is more economical in its manufacture.